Pollution Load Estimation and Control Countermeasures of Zhangze Reservoir - Yang, Long; Zhang, Min; Wei, Jia; Qi, Jun (Frontiers in Environmental Science, 2022)
Raising the water pollution control countermeasures on the basis of rational pollution load estimation is significant for improving water quality. Zhangze Reservoir, the largest water body in Changzhi city, China, was selected for this study. Considering the information constraints of the reservoir basin, the pollution load estimation method system covering point sources, non-point sources, and internal sources is systematically constructed using an export coefficient model, an sediment pore water diffusion model, and other methods, with the aim of estimating the discharge of pollutants into the Zhangze Reservoir from domestic sources, industrial sources, agricultural sources, sediment release, and urban runoff. The findings indicate the following: 1) the pollution loads of COD, NH3-N, TN, and TP are 3,157.82t, 177.62t, 760.72t, and 42.29t, respectively; 2) in terms of the distribution of pollution sources, urban domestic sources top the rest, accounting for 65.47% of COD, 82.83% of NH3-N, 79.00% of TN, and 60.65% of TP, followed by the agricultural source; 3) the total discharge of the main water pollutants exceeds the water environmental capacity, characterized as the dominating existence of domestic point source, the coexistence of point sources and non-point sources, and the coexistence of exogenous sources and endogenous sources. Finally, control countermeasures are raised to minimize the total discharge of pollutants for improving the water quality.